2023
DOI: 10.3390/nu15030763
|View full text |Cite
|
Sign up to set email alerts
|

Meal Timing and Sleeping Energy Metabolism

Abstract: There is a physiological link between sleep and eating. Insufficient sleep is a risk factor for overeating and excess body weight gain, and molecules such as orexin and insulin play a role in the control of sleep and energy intake. The effects of dietary timing on sleep and energy metabolism were examined in this review. First, we examined sleep energy metabolism and sleep quality under time-restricted eating, including skipping breakfast or dinner. Second, the mechanisms, benefits, and translational potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Although there are no previous studies that have used TEM to analyze the effects of circadian eating timing on sleep, the study that first proposed it 31 was justified by the consequences of evening eating on circadian misalignment, previously highlighted by numerous experimental and observational studies. 25,26,[34][35][36][37][38][39] Both evening eating and evening latency, defined as the duration of time between the last eating event and sleep onset, are part of chrononutritional behaviors that can misalign the phase of an individual's circadian rhythm and negatively influence health. 34,35 Findings suggested that eating late and close to bedtime may contribute to poor sleep and misalignment of the melatonin phase, 22,23 besides affecting weight, weight-related health outcomes such as insulin resistance, metabolic disease, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are no previous studies that have used TEM to analyze the effects of circadian eating timing on sleep, the study that first proposed it 31 was justified by the consequences of evening eating on circadian misalignment, previously highlighted by numerous experimental and observational studies. 25,26,[34][35][36][37][38][39] Both evening eating and evening latency, defined as the duration of time between the last eating event and sleep onset, are part of chrononutritional behaviors that can misalign the phase of an individual's circadian rhythm and negatively influence health. 34,35 Findings suggested that eating late and close to bedtime may contribute to poor sleep and misalignment of the melatonin phase, 22,23 besides affecting weight, weight-related health outcomes such as insulin resistance, metabolic disease, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Findings suggested that eating late and close to bedtime may contribute to poor sleep and misalignment of the melatonin phase, 22,23 besides affecting weight, weight-related health outcomes such as insulin resistance, metabolic disease, and inflammation. 31,[35][36][37][38][39] In a cross-sectional examination of the young Japanese population under free-living conditions, shortened time from dinner to bedtime was associated with prolonged sleep latency. 22 In a Brazilian study, healthy participants completed a 3-day food diary and underwent polysomnography, and findings showed that food intake within 30 to 60 minutes of bedtime was associated with delayed sleep onset and decreased sleep efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, different compositions in gut microbiota are observed in males and females ( 27 ) and may play a role in gender differences in the regulation of appetite. In addition, an association between food intake, meal timing and sleep disturbances has been suggested ( 28 ). Accordingly, sleep quality emerges as a key element of overall well-being, which is greatly influenced by body composition ( 29 ).…”
Section: Discussionmentioning
confidence: 99%